Red-light emissive phosphorescent polymers based on X-shaped single benzene. (February 2022) - Wu, Yanan; Gui, Huiqiang; Ma, Liangwei; Zou, Lei; Ma, Xiang
Abstract: Recently, the single benzene molecule has attracted widespread attention in room temperature phosphorescence (RTP) materials for its simple structure. However, it is difficult to achieve the long wavelength emission and there are few feasible, universal strategies to construct phosphors with long wavelength emission. In this study, a series of X-shaped phosphors derived from tetrafluoroterephthalonitrile were synthesized and copolymerized with acrylamide to obtain RTP materials. Polymers containing selenium (Se) atoms exhibited long wavelength RTP emission around 600 nm and over 200 nm Stokes shift. PN1, the fluorescence and phosphorescence dual emission material, exhibited red phosphorescence emission at 605 nm. Theoretical calculation was performed to explain the underlying reasons for the produce of phosphorescence. Graphical abstract: Image 1 Highlights: Single benzene structures with red phosphorescent emission around 605 nm. A feasible, and simple cocktail approach toward phosphors based on X-shaped single benzene. Dual emission phosphors with fluorescence around 500 nm and phosphorescence around 600 nm.